Associations of body mass index with mortality in heart failure with preserved ejection fraction patients with ischemic versus non-ischemic etiology - Zeng, Shan; Cai, Xingming; Zheng, Yuxiang; Liu, Xiao; Ye, Min (Frontiers in Cardiovascular Medicine, 2022)
Background: Obesity could paradoxically improve prognosis in patients with heart failure (HF), termed the "obesity paradox". Whether HF etiology could modify the “obesity paradox” is still controversial. In the present study, we aimed to assess the relationship between obesity and death in patients with heart failure with preserved ejection fraction (HFpEF) with non-ischemic versus ischemic etiologies. Methods: We analyzed 3,360 HFpEF patients from the TOPCAT trial. Cox regression models were used to assess the association of obesity assessed by body mass index (BMI) with short-term and long-term death risk. Results: Overweight and obesity were associated with a lower risk of long-term all-cause death in patients with non-ischemic HFpEF, even in those with class III obesity (adjusted HR: 0.61, 95%CI 0.38-0.97). However, in the ischemic subgroup, as obesity advanced, this paradoxical relationship was gradually attenuated and disappeared in class III obesity (adjusted HR: 0.93, 95%CI 0.56-1.57). Restricted cubic spline analyses confirmed the differential relationship of baseline BMI with risk of long-term death with a BMI higher than 30 kg/m2 in non-ischemic versus ischemic HFpEF. In the short-term follow-up, the beneficial effects of overweight and obesity on survival were consistently observed in all the BMI categories, with the nadirs of all-cause death risk at class III obesity category both in non-ischemic and ischemic subgroups. Conclusions: “Obesity paradox” was evident both in non-ischemic and ischemic HFpEF during short-term follow-up, even in those with class III obesity. However, the beneficial effect of class III obesity disappeared during long-term follow-up in ischemic HFpEF.